Gaucho Gazette: speech and sensationalism: discurso e sensacionalismo - Ramos, Roberto José (2013)
The Gaucho Gazette presents itself as a “popular newspaper”. Attempts to produce a denial about his aesthetic tabloid. Search only say that discloses what happens, as if the media were merely a reflection of society. This paper will seek to understand and explain your Sensationalism, through their speeches. Use for both, semiology, Roland Barthes, in their possibilities transdisciplinary.